(untitled) (Journal of the Society for Musicology in Ireland, 2022)
This paper builds upon the work of Hogan (2016, 2021) by casting a historical lens on the importance of emotional connectivity to place in Cork through a case study of the city’s most famous musician: the blues/rock guitarist Rory Gallagher. Specifically, it investigates how sense of place and Corkonian values are narratively produced and depicted in the Irish Tour ’74 documentary. It argues that the documentary portrays County Cork as a close-knit place with a deep sense of community and Gallagher as the physical representation of these values. Analysis of specific scenes also highlights the significance of localist expressions of identity and localised forms of prestige for Gallagher, as well as the way in which his songs can be renarrativised to create new meanings that either accentuate his yearning for home or promote a form of hybridised parochialism that centres around Belfast as his ’second home’. Acknowledgements I am extremely grateful to Rory’s brother Dónal Gallagher and nephew Daniel Gallagher for their permission to use stills from the Irish Tour ’74 documentary in this paper.